Thermosolutal convection in ferromagnetic fluid (Archives of Mechanics - Test, 2004)
The thermosolutal convection in ferromagnetic fluid is considered for a fluid layer heated and soluted from below in the presence of uniform vertical magnetic field. For the case of two free boundaries, an exact solution is obtained using a linear stability analysis. For the case of stationary convection, magnetization has a destabilizing effect, whereas stable solute gradient has a stabilizing effect on the onset of instability. Graphs have been plotted by giving numerical values to various parameters, to depict the stability characteristics. The principle of exchange of stabilities is found to hold true for the ferromagnetic fluid heated from below in porous medium in the absence of stable solute gradient. The oscillatory modes are introduced due to the presence of the stable solute gradient, which were non-existent in its absence. A sufficient condition for non-existence of the overstability is also obtained.